2010
DOI: 10.1007/s11738-009-0443-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced salinity tolerance and improved yield properties in Bangladeshi rice Binnatoa through Agrobacterium-mediated transformation of PgNHX1 from Pennisetum glaucum

Abstract: Rice yield is severely affected by high-salt concentration in the vicinity of the plant. In an effort to engineer rice for improved salt tolerance Agrobacteriummediated transformation of rice cv. Binnatoa was accomplished with the Pennisetum glaucum vacuolar Na ? /H ? antiporter gene (PgNHX1) under the constitutive CaMV35S promoter. For the molecular analysis of putative transgenic plants, PCR and RT-PCR were performed. Transgenic rice plants expressing PgNHX1 showed better physiological status and completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Our results on Na + accumulation are in disagreement with the most recent study, , who reported a higher accumulation of Na + in the leaves of transgenic plants, including transgenics harbouring TaNHX1, compared to WT plants under 200 mM salt treatment. However, our results are in line with those reported by Islam et al (2010) who demonstrated that the over-expression of Pennisetum glaucum vacuolar antiporter gene (PgNHX1) in rice led to significantly higher leaf content of K + and less Na + in transgenic plants as compared to wild type plants. Similar results were also reported by Zhao et al (2007) and Wei et al (2010).…”
Section: Discussionsupporting
confidence: 93%
“…Our results on Na + accumulation are in disagreement with the most recent study, , who reported a higher accumulation of Na + in the leaves of transgenic plants, including transgenics harbouring TaNHX1, compared to WT plants under 200 mM salt treatment. However, our results are in line with those reported by Islam et al (2010) who demonstrated that the over-expression of Pennisetum glaucum vacuolar antiporter gene (PgNHX1) in rice led to significantly higher leaf content of K + and less Na + in transgenic plants as compared to wild type plants. Similar results were also reported by Zhao et al (2007) and Wei et al (2010).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with our previous observation of lower Na + in leaves of salt tolerant cowpea transgenics, overexpressing VrNHX1 (Mishra et al, 2014 ). Similar phenomena of lower Na + in leaves transgenic plants overexpressing NHXs genes was also reported in rice (Islam et al, 2010 ), soybean (Li et al, 2010 ). In the transgenic plants examined, the salt-tolerant phenotype was associated with a lower K + content in leaves and roots relative to WT plants.…”
Section: Discussionsupporting
confidence: 81%
“…However, transgenic switchgrass accumulated significantly higher K + and lower Na + in all tissues compared with control plants (Figure 7), which failed to detect the significant correlation between enhanced salt tolerance and increased accumulation of Na + . The presence of lower Na + in transgenic plants overexpressing NHXs genes was also reported in rice (Islam et al, 2010), soybean (Li et al, 2010), and cowpea (Mishra et al, 2014), These resules challenged the widely accepted notion that NHXs convey salt tolerance by enhancing Na + sequestration into vacuoles, indicating a different regulatory pathways of NHXs in salt tolerance might exist. This speculation was supported by the evidence from recent reverse genetics, in which the critical role of NHXs in K + homeostasis to withstand salt shock was confirmed (Bassil et al, 2011; Barragán et al, 2012; Andrés et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…In plants, the sequestration of Na + in vacuole had been identified as an important mechanism to salt tolerance (Apse et al, 1999). However, recent studies have found the opposite result in transgenic rice (Islam et al, 2010), soybean (Li et al, 2010), and cowpea (Mishra et al, 2014), that greater K + , rather than Na + contents were observed under salinity stress. Emerging new reverse genetics evidence has also implicated that NHXs were not indispensable for Na + uptake into vacuoles of Arabidopsis , and confirmed their main role in the regulation of K + homeostasis (Bassil et al, 2011; Barragán et al, 2012; Andrés et al, 2014).…”
Section: Introductionmentioning
confidence: 97%